2023
DOI: 10.1002/advs.202302905
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐Responsive Hydrogel Spray for Synergistic Prevention of Traumatic Heterotopic Ossification via Dual‐Homeostatic Modulation Strategy

Jiazhao Yang,
Xudong Zhang,
Baoliang Lu
et al.

Abstract: Traumatic heterotopic ossification (THO) represents one of the most prominent contributors to post‐traumatic joint dysfunction, which currently lacks an effective and definitive preventative approach. Inflammatory activation due to immune dyshomeostasis during the early stages of trauma is believed to be critical in initiating the THO disease process. This study proposes a dual‐homeostatic modulation (DHM) strategy to synergistically prevent THO without compromising normal trauma repair by maintaining immune h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, its poor solubility and rapid hydrolytic degradation in aqueous solution severely impede its clinical applications. Although many encapsulation methods or delivery vehicles have been developed, the controlled release of pharmaceutical ingredients at the site of action remains a major challenge. Curcumin has the ability to inhibit the growth of Helicobacter pylori and reduce the incidence of gastric cancers. , Considering the extremely acidic environment in the stomach, investigating the pH-controlled curcumin release from IIIGGHK assemblies is valuable for its applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, its poor solubility and rapid hydrolytic degradation in aqueous solution severely impede its clinical applications. Although many encapsulation methods or delivery vehicles have been developed, the controlled release of pharmaceutical ingredients at the site of action remains a major challenge. Curcumin has the ability to inhibit the growth of Helicobacter pylori and reduce the incidence of gastric cancers. , Considering the extremely acidic environment in the stomach, investigating the pH-controlled curcumin release from IIIGGHK assemblies is valuable for its applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The ZC-DOX NPs were synthesized using the previously reported method 25 . They exhibited a spherical structure with a size of approximately 102 nm, as observed through scanning electron microscopy (SEM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of DOX@ZIF-8@ CeO 2 (ZC-DOX) followed a previously reported procedure with some adaptations 25 . Specifically, 500 mg of 2-methylimidazole and 5 mg of doxorubicin were combined in 4 mL of methanol and stirred for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the myotube content represented by a high concentration of crystal violet was significantly reduced in the HG group, while the intervention of CNPs promoted myotube formation in C2C12 cells. 21 Combined with the regulation of IL-1β by CNPs and based on the previous findings, the reason for this discrepancy may be that CNPs inhibit the expression and release of IL-1β, which further inhibits the activation of the NLRP3 inflammasome and the downstream inflammatory disturbances within the myocytes, thus maintaining myocyte homeostasis. 22 3.4.…”
Section: Cnps Maintain Redox Homeostasis In Myofibroblasts In Vitromentioning
confidence: 96%